PHACTR1 gene polymorphism with the risk of coronary artery disease in Chinese Han population. Issue 1120 (18th February 2019) - Chen, Lishan; Qian, Hang; Luo, Zhihuan; Li, Dongfeng; Xu, Hao; Chen, Jishun; He, Peigen; Zhou, Xintao; Zhang, Tao; Chen, Jun; Min, Xinwen
Abstract: Background: Coronary artery disease (CAD) is the most frequent multifactorial disease worldwide and is characterised by endothelial injury, lipid deposition and coronary artery calcification. The purpose of this study was to determine the allelic and genotypic frequencies of two loci (rs2026458 and rs9349379) of phosphatase and actin regulator 1 (PHACTR1) to the risk of developing CAD in the Chinese Han population. Methods: A case–control study was conducted including 332 patients with CAD and 119 controls. Genotype analysis was performed by PCR and Sanger sequencing. Genetic model analysis was performed to evaluate the association between single nucleotide polymorphisms and CAD susceptibility using Pearson's χ 2 test and logistic regression analysis. Results: The GG genotype of rs9349379 represented 50% and 29% of patients with CAD and controls, respectively (p<0.001). The CC genotype of rs2026458 was more prevalent in the controls than in patients with CAD compared with TT genotype (OR=0.548, 95% CI 0.351 to 0.856, p=0.008). Logistic regression analyses revealed that PHACTR1 rs9349379 GG genotype was significantly associated with increased risk of CAD in the recessive model (OR=2.359, 95% CI 1.442 to 3.862, p=0.001), even after adjusting for age gender, hypertension, type 2 diabetes, hyperlipidaemia and smoking habit. Heterogeneity test proved that rs9349379's risk effects on CAD were more significant among women. Conclusions: Our study indicate that the PHACTR1 rs9349379 polymorphism is associated with the increased risk for CAD in the female Chinese Han population.